A Targeted Nanosystem for Detection of Inflammatory Diseases via Fluorescent/Optoacoustic Imaging and Therapy via Modulating Nrf2/NF‐κB Pathways. Issue 42 (14th September 2021) - Ouyang, Juan; Sun, Lihe; Pan, Jiayue; Zeng, Zhuo; Zeng, Cheng; Zeng, Fang; Tian, Mei; Wu, Shuizhu
Abstract: Inflammatory diseases are sometimes devastating and notoriously difficult to treat. Precisely modulating inflammatory signaling pathways is a promising approach for treating inflammatory diseases. Herein, a multifunctional nanosystem is developed for active targeting, activatable imaging and on‐demand therapy against inflammatory diseases through modulating inflammatory pathways. A chromophore‐drug dyad (QBS‐FIS) is synthesized by linking a chromophore and a Nrf2 (nuclear factor E2‐related factor) activator fisetin through boronate bond which serves as fluorescence quencher and ROS (reactive oxygen species)‐responsive linker. QBS‐FIS molecules form nanoparticles in water and are coated with macrophage cell membrane to ensure active targeting toward inflammation site. To further improve therapeutic efficacy, a NF‐ k B (nuclear‐factor kappa‐light‐chain‐enhancer of activated B cells) inhibitor thalidomide is co‐encapsulated to afford the nanosystem (QBS‐FIS&Thd@MM). Upon administration into mice, the nanosystem migrates to inflammatory site and pathological ROS therein cleaves the boronate bonds, thereby activating the chromophore for imaging liver/kidney inflammatory diseases for disease diagnosis and recovery evaluation via fluorescence and optoacoustic imaging as well as releasing the active drugs for treating acute liver inflammation through activating Nrf2 pathway and inhibiting NF‐ k B pathway. The 3D multispectral optoacoustic tomography imaging is applied to precisely locate the inflammatory foci in a spatiotemporal manner. Abstract : A nanosystem with active targeting capability has been developed for imaging liver/kidney inflammation and treating liver inflammation. Triggered by reactive oxygen species, the nanosystem activates a chromophore for diagnosis and therapeutic efficacy evaluation via fluorescence/optoacoustic imaging, and releases drugs for therapy through modulating Nrf2 (nuclear factor E2‐related factor) and NF‐κB (nuclear‐factor kappa‐light‐chain‐enhancer of activated B cells) pathways.